"On our own, we can't manage": experiences with infant feeding recommendations among Malawian mothers living with HIV - Levy, Jennifer M (BioMed Central, 2010)
BACKGROUND: Infant feeding in communities with a high prevalence of HIV and AIDS is a potential challenge for mothers who must ultimately decide how to feed their infants within contexts that constrain their choices. METHODS: We investigated how infant feeding policy recommendations translate into maternal infant feeding decisions and practices using ethnographic research conducted between August 2004 and June 2005 among women participating in a prevention of mother-to-child transmission (PMTCT) program in Lilongwe, Malawi. RESULTS: Qualitative findings are that maternal ability to adhere to recommendations to breastfeed exclusively for the first six months of infant life was constrained by expectations and psycho-social support. The most salient were women's pre-existing views on breastfeeding, their understanding of the medico-scientific information, and the quality of counselling received. In contrast, maternal decisions to wean were largely influenced by household economic factors and food insecurity. CONCLUSIONS: We conclude that PMTCT programs delivered in ways which "download" the responsibility of adhering to recommendations to women in the absence of adequate psycho-social and livelihood supports contribute to substantial maternal psychosocial distress in this and, likely, similar settings.